Carcass attributes in breeding objectives and selection criteria for british breeds in Uruguay - Urioste, J. I.; Ponzoni, R. W.; Aguirrezabala, M.; Rovere, G.; Saavedra, D. (Agrociencia Uruguay, 2003)
This study considered the inclusion of carcass attributes in breeding objectives and selection criteria developed for pasture-fed Uruguayan production systems for beef cattle, based on British breeds. Correlated responses in dressing percentage (DP), eye rib area (ERA) and dorsal fat depth (DFD) were determined, when these traits are not formally included in the breeding objective. Addition of DP in the breeding objective, which also included growth, reproduction and feed intake traits, was studied. Genetic change in each trait when using selection indices that included growth (G), growth plus reproduction (GR) and growth plus reproduction plus carcass measures (GRC, where ERA and DFD were obtained by ultrasound techniques) was evaluated. The correlated response in carcass traits when they were not included in the breeding objective was insignificant or very small. When included in the breeding objective, DP showed the lowest economic-genetic importance in relation to other growth, reproduction and feed intake traits. Index GR showed a genetic gain of 94% over that produced by index G, whereas index GRC only showed a superiority of 16% over index GR. Carcass attributes are not expected to deteriorate, even when they were not included in the breeding objective. Inclusion of DP as the only carcass trait in the objective is of secondary importance in beef cattle selection.